Does aquaculture of Mastocarpus stellatus in an IMTA impact on the chemical and rheological properties of extracted carrageenans - Hilliou, L. (2013)
The bio filtration potential of Mastocarpus stellatus, a commercially attractive carrageenophyte for foods and pharmaceutics, was investigated by cultivating the seaweeds in the nutrient-rich outflow of a commercial fish farm. Results from two consecutive 4 weeks experiments indicate that the cultivation of this seaweed allows algal growth with satisfactory nutrient removal, independent of tested cultivation conditions. DRIFT and CP-MAS NMR analyses of seaweeds indicate that one month cultivation affects quantitatively the seaweeds chemistry, and thus the chemical and gelling properties of native extracts of kappa/iota-hybrid carrageenan (KI). However, the enhanced gelling properties of alkali-extracted KI are not affected, and compare well with the gelling properties of alkali-extracted KI from wild seaweeds [1]. This study demonstrates the capacity of growing M. stellatus in an Integrated Multi-Trophic Aquaculture system for bioremediation and the sustainable production of high value polysaccharides. [1] Azevedo, G., Hilliou, L., Bernardo, G., Sousa Pinto, I., Adams, R. W., Nilsson, M., Villanueva, R. D. 2013. Tailoring kappa/iota-hybrid carrageenan from Mastocarpus stellatus with desired gel quality through pre-extraction alkali treatment. Food Hydrocolloid. 31, 94-102.